(untitled) (Indian Journal of Arid Horticulture, 2025)
Collar rot of kagzi lime (Citrus aurantifolia, Swing.) is caused by Rhizoctonia solani Kuhn. In nursery stage, about 40- 55% seedlings of Kagzi lime (Citrus aurantifolia Swing) were died due to collar rot. This is the first report of collar rot diseases in Kagzi lime caused by R. solani from the nursery of Uttar Pradesh. The efficacy of three Trichoderma species viz T. harzianum, T. virens and T. viride against R. solani were tested by dual culture technique. T. virens and T. viride grew very fast before touching the colony of the R. solani, thereafter; their growth was significantly slowed down. But T. harzianum grew very fast over the colony of R. solani, and completely covering it within 8 days. The population of R.solani in infested soil could be minimized by treating the soil with T. harzianum, T. virens and T. viride. T. harzianum and T. virens grew very fast and occupied the space and consumed nutrients in the root rhizosphere, thus, outwitted the pathogen.